Orang Dengan Gangguan Jiwa (ODGJ) Sebagai Korban Tindak Pidana : Bagaimana Aturan Hukum Pidananya? - Pradea, Regina; Haryadi, Haryadi; Arfa, Nys (PAMPAS: Journal of Criminal Law, 2024)
This article aims to analyze the legal protection regulations for people with mental disorders as victims. Serious health problems worldwide are mental and mental disorders. People with mental disorders (ODGJ) experience stigmatization and discrimination which makes them easy victims of acts of violence. In Indonesia, there are around 2.5 million people who experience mental disorders and about 60% of them are at risk of experiencing violent behavior. The research method used is a normative juridical research type. The results of this research article are People with Mental Disorders (ODGJ) Individuals who are victims of crime will still be given legal protection in accordance with the provisions contained in Law Number 31 of 2014 which amends Law Number 13 of 2006 concerning Protection of Witnesses and Victims and Law Number 18 of 2014 concerning Mental Health. Legal protection will also be provided to ensure the rights of people with mental disorders (OMGJ) are protected. Being a victim has not been fully realized, so the government must be more concerned about all forms of legal protection for people with mental disorders (ODGJ). Abstrak Artikel ini bertujuan untuk menganalisis regulasi perlindungan hukum orang dengan gangguan jiwa sebagai korban. Masalah kesehatan yang serius di seluruh dunia adalah gangguan jiwa dan mental. Orang dengan gangguan jiwa (ODGJ) mengalami stigmatisasi dan diskriminasi yang membuat mereka mudah menjadi korban tindakan kekerasan. Di Indonesia, terdapat sekitar 2,5 juta orang yang mengalami gangguan jiwa dan sekitar 60% dari mereka berisiko mengalami perilaku kekerasan. Metode penelitian yang digunakan adalah tipe penelitian Yuridis Normatif. Hasil penelitian artikel ini adalah Orang Dengan Gangguan Jiwa (ODGJ) Individu yang menjadi korban kejahatan masih akan diberikan perlindungan hukum sesuai dengan ketentuan yang tercantum dalam Undang-Undang Nomor 31 Tahun 2014 yang mengubah Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban serta Undang-Undang Nomor 18 Tahun 2014 tentang Kesehatan Mental. Perlindungan hukum juga akan diberikan untuk memastikan hak-hak Orang yang Mengalami Gangguan Jiwa (OMGJ) terlindungi. Sebagai korban belum sepenuhnya terealisasikan, sehingga pemerintah harus lebih peduli terhadap segala bentuk perlindungan hukum terhadap Orang Dengan Gangguan Jiwa (ODGJ).